Impact of oral medicine training on oral cancer-related knowledge among undergraduate dental students - Gisele Reisdoerfer Galina; Gilmar José Begnini; Flares Baratto Filho; Juliana Feltrin de Souza; Carla Castiglia Gonzaga; Melissa Rodrigues de Araujo (Universidade Estadual de Campinas, 2019)
Aim: The aim of this study was to evaluate knowledge and attitudes regarding potentially malignant oral lesions and oral cancer among undergraduate dental students with or without training in the oral medicine. Methods: A cross-sectional study was undertaken to assess all undergraduate dental student (1st to 5th year) in two private universities in the state of Paraná, Brazil. A structured questionnaire about knowledge regarding potentially malignant oral lesions, continuing education, and different approaches to diagnosis was administered to dental students with or without training in the oral medicine discipline between May and July 2015. Descriptive statistics were obtained, and the data were analyzed using a chi-square test to compare knowledge in dental students. Results: A total of 662 undergraduate dental students were invited to participate, and the response rate was 97.6% (n = 646). Of the responders, 472 were female (73.1%), 168 were male (26.0%), and 6 did not declare what sex they were (0.9%). Undergraduate dental students who had previously studied oral medicine  tended to report  that they always perform complete intraoral examination (76.3%) and identified alcohol (87%) and tobacco consumption (97%) and sun exposure (80%) as major risk factors for developing oral cancer. While students who had not yet studied oral medicine poorly identified these factors. Students who had previously studied the discipline did not identify cheilitis actinica (26%) and erythroplakia (32%) as potentially malignant lesions. Only, 32.6% of dental students participate in continuing education during the past year. Conclusions: Dental students trained in the oral medicine discipline exhibited satisfactory knowledge necessary for the prevention and early identification of potentially malignant oral lesions and oral cancer. Continuing education during undergraduate and after academic training is very important.